Surface treatment of an applied novel all-diamond microchannel heat sink for heat transfer performance enhancement. (August 2020) - Qi, Zhina; Zheng, Yuting; Wei, Junjun; Yu, Xingang; Jia, Xin; Liu, Jinlong; Chen, Liangxian; Miao, Jianyin; Li, Chengming
Graphical abstract: Highlights: An applied AD-MCHS was processed on an ultra-thick CVD diamond plate. The extra pressure-drop of merely <5% at large Reynolds number was negligible. 20–50% increase of HTC was realized after surface hydrophilization. 14–28% reduction of thermal resistance was obtained by surface modification. The minimum thermal resistance of 0.28 °C/W can be obtained. The maximum temperature-drop of 11.49℃ of heat source surface was achieved. Abstract: Diamond with superior thermal conductivity would effectively unlock the heat dissipation problem, while the all-diamond microchannel heat sink (AD-MCHS) is immature. In the present work, surface modification of an applied novel AD-MCHS for heat transfer enhancement associate with single-phase (deionized water) coolant was elucidated, for the first time, on an ultra-thick free-standing chemical vapor deposition (CVD) diamond plate. The heat transfer performance of as-processed and post-treated AD-MCHS by surface oxygen-introduction were systematically studied under three heat flux levels, i.e., 40 W/cm 2, 80 W/cm 2 and 120 W/cm 2, respectively. The results demonstrated that the heat transfer performance of the AD-MCHS after acid post-treatment (which was a preferable manner comparing with oxygen plasma and H2 O2 bath) was prominently enhanced: 20–50% improvement of heat transfer coefficient (to the maximum of 11917 W/m 2 ·K), 14–28% reduction of thermal resistance and minimum thermal resistance of 0.28 °C/W as well as maximum temperature drop of 11.49 °C for heat source surface. These were the results of hydrophilic diamond surface associated with stronger surface interaction with water molecules, resulting from the reconstructed surface polar carbon-oxygen components, removal of surface graphitic phases as well as the accompanying temperate rising of surface roughness. And the heat transfer acting a more important factor would be enhanced at the expense of acceptable steadily increasing pressure drop (about 1 kPa) and negligible extra of merely <5% with the rising of Reynolds number.